A method for preparing a sodium-contaminated molecular sieve
Patent Information
- Application Number
- CN202211723991.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-12-30
AI Technical Summary
该技术通过大比表面载体负载钠离子的方式可以减轻分子筛上的钠离子负载,但并不能有效解决分子筛的抗钠性能,对于不同钠含量环境适应性较差
[0019]本发明所述方法在分子筛中引入金属阳离子与分子筛表面的酸性中心相互作用,进而稳定酸性中心,同时其自身作为一种牺牲剂,在高苛刻度交换下,会少量流失(污染前后降低0.1-0.2wt%的负载量),以保护分子筛表面的酸性中心避免Na污染,同时本方法可以分散金属的同时引入少量模板剂起到对表面阻碍负载的同时,实现金属最大化在孔道内分散,与P相结合,实现孔道内酸性中心最大化的抗污染能力。并且,该抗Na污染的分子筛引入的金属阳离子与分子筛表面形成的酸性中心相互作用的同时,更容易与Na离子相结合,从而将Na离子更多的吸引到非酸性中心避免试验过程中酸性中心的毒化效应,因而制备的催化裂化催化剂在工业应用中,可以有效避免Na污染导致催化剂活性的大幅降低。
Smart Images

Figure BDA0004029003960000091 
Figure BDA0004029003960000111 
Figure BDA0004029003960000112
Abstract
Description
Technical Field
[0001] This invention belongs to the field of molecular sieve technology, and specifically relates to a method for preparing a sodium-resistant molecular sieve. Background Technology
[0002] Molecular sieves, as non-toxic and pollution-free inorganic materials, are popular active materials in the field of catalytic cracking for increasing the yield of low-carbon olefins due to their excellent shape selectivity. ZSM-5 molecular sieves have a relatively low number of acidic centers. During catalytic cracking reactions, the acidic centers on the surface of the ZSM-5 molecular sieve mainly serve as active centers. However, in the preparation process of catalytic cracking catalysts, especially in industrial production, the introduction of Na ions is unavoidable in both the raw materials and the industrial water used for catalyst production, leading to the loss of acidic centers on the molecular sieve surface. Furthermore, for cracking feedstocks with high Na content (such as crude oil and high-Na heavy oil), direct use in catalytic cracking also reduces the number of acidic centers in the molecular sieve, resulting in a decrease in the yield of low-carbon olefins. Therefore, developing a Na-resistant ZSM-5 molecular sieve technology can be used to prepare highly stable, high-selectivity catalytic cracking catalysts for low-carbon olefins.
[0003] Patent CN102050458A discloses a modified molecular sieve and its preparation method to improve sodium contamination resistance. The method involves adding the molecular sieve to a phosphorus-containing organic solution and reacting it for 10-200 minutes at a reaction temperature of 70-200℃ and a reaction pressure of 0.2-1.2 MPa. After filtration, drying, and calcination, a shape-selective molecular sieve with a phosphorus oxide content of 1-10% is obtained. This molecular sieve exhibits good sodium contamination resistance, and the sodium-contaminated model catalyst retains a high activity rate. However, this technique uses organic solvent loading, which is costly. Furthermore, conventional aqueous solution loading limits the sodium resistance of the molecular sieve. Significantly increasing the phosphorus oxide loading to ensure sodium contamination resistance leads to excessive loss of acidic centers and blockage of the molecular sieve channels, resulting in a decrease in the yield of low-carbon olefins. Additionally, phosphorus loading comes at the cost of sacrificing active centers on the molecular sieve surface.
[0004] Patent CN86107598A discloses a hydrocarbon catalytic cracking catalyst containing a rare-earth ultrastable Y-type molecular sieve. RE₂O₃ is mixed into the molecular sieve slurry, ensuring that all rare-earth elements in the molecular sieve exist in the form of Re(OH)₃ or RE₂O₃. This cracking catalyst exhibits resistance to sodium and heavy metal contamination and is suitable for catalytic cracking or hydrocracking of heavy oil, especially heavy oil with high sodium content. While this invention effectively resists sodium and reduces olefin content in gasoline components by introducing rare-earth elements into traditional catalytic cracking catalysts, under the current catalytic cracking technology targeting low-carbon olefins, the introduction of rare-earth elements into the molecular sieve exacerbates hydrogen transfer reactions, leading to secondary reactions of low-carbon olefin products and reducing the catalyst's selectivity for low-carbon olefins. Therefore, this method is unsuitable for catalytic cracking catalysts targeting low-carbon olefins.
[0005] Patent CN114715911A discloses a method for preparing a phosphorus-containing and metal-containing hierarchical porous ZSM-5 molecular sieve. The method involves first contacting a phosphorus-containing compound solution with a hydrogen-form ZSM-5 molecular sieve, followed by drying. Then, the sieve undergoes hydrothermal calcination under external pressure and with added water to recover the product, resulting in a phosphorus-containing hierarchical porous ZSM-5 molecular sieve. Next, a metal is loaded onto the phosphorus-containing hierarchical porous ZSM-5 molecular sieve using a commonly used method in the art: impregnating the molecular sieve with a metal compound solution followed by calcination. The metal is selected from one or more of the VIII, IIB, VIIB, IIIA, IVA, and lanthanides. The metal content, calculated as oxides, is 0.1–10% by weight. The molar ratio of the phosphorus-containing compound (calculated as phosphorus) to the hydrogen-form hierarchical porous ZSM-5 molecular sieve (calculated as aluminum) is 0.01–2, preferably 0.1–1.5, and more preferably 0.3–1.3. The key to this invention is the high-temperature introduction of phosphorus (P) onto a multi-level porous molecular sieve. The purpose is to stabilize the loading of P on the surface of the molecular sieve. At the same time, the conventional low-temperature method of introducing metal can effectively enhance the hydrocarbon activation ability of the molecular sieve. However, the location and dispersion of the metal loading are uncertain.
[0006] The literature "Development and Industrial Application of Sodium-Resistant FCC Catalysts" (Zhang Xin, Zhu Huayuan, Zhang Juewu, Ran Yun. Refining Design, 1997(02):58-60.) discloses a method for preparing sodium-resistant FCC catalysts. This method primarily involves introducing a large specific surface area support during catalyst preparation. A larger specific surface area of the support contributes to the catalyst's sodium resistance. This is related to the fact that a higher specific surface area of the support can load more sodium ions, thus reducing the sodium content on the molecular sieve. While this technique can alleviate the sodium ion load on the molecular sieve by loading sodium ions onto a large specific surface area support, it cannot effectively solve the sodium resistance problem of the molecular sieve and exhibits poor adaptability to environments with varying sodium content. Summary of the Invention
[0007] The purpose of this invention is to provide a method for preparing sodium-resistant molecular sieves. The molecular sieves prepared by this method have good sodium-resistant properties and are suitable for preparing highly stable, high- and low-carbon olefin selective catalytic cracking catalysts.
[0008] To achieve the above objectives, the present invention provides a method for preparing a sodium-resistant molecular sieve, wherein the molecular sieve is impregnated with a precursor solution containing phosphorus anions, and dried to obtain a phosphorus-modified molecular sieve; the phosphorus-modified molecular sieve is impregnated with a precursor solution containing metal cations and an alkaline organic ammonium salt solution, and then dried and calcined to obtain a sodium-resistant molecular sieve.
[0009] The method for preparing sodium-resistant selective molecular sieves according to the present invention refers to a molecular sieve with acidic centers on its surface. The specific type is not specifically limited. Preferably, the molecular sieve of the present invention is one or more of ZSM-5 molecular sieve, Y molecular sieve, and β molecular sieve.
[0010] The method for preparing sodium-resistant selective molecular sieves according to the present invention uses alkaline organic ammonium salts, which are commonly used substances in the field and are not limited to specific types. Preferably, the alkaline organic ammonium salts of the present invention are one or more of tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, benzyltrimethylammonium hydroxide, tetraethylammonium hydroxide, and tetramethylammonium hydroxide.
[0011] The method for preparing the sodium-resistant selective molecular sieve of the present invention wherein the mass ratio of the alkaline organic ammonium salt to the phosphorus-modified molecular sieve is 0.01-0.5.
[0012] The method for preparing sodium-resistant selective molecular sieves according to the present invention uses phosphorus-containing anion precursors that are commonly used in the art, and the specific type is not limited. Preferably, the phosphorus-containing anion precursors of the present invention are one or more of ammonium phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, phosphoric acid, and ammonium trihydrogen phosphate. The concentration of the phosphorus-containing anion precursor solution during loading depends on the amount of phosphorus loaded, and those skilled in the art can select and adjust it according to conventional technical knowledge in the field; the present invention does not impose specific limitations.
[0013] In the preparation method of the sodium-resistant selective molecular sieve of the present invention, the phosphorus loading is 1-5 wt% of the molecular sieve mass, calculated as oxide.
[0014] The method for preparing sodium-resistant selective molecular sieves according to the present invention uses a precursor containing metal cations, wherein the metal is one or more of Fe, Co, Ni, Zn, Mg, and Cu, preferably one or more of Co, Zn, and Mg. The type of precursor containing metal cations is not specifically limited, such as nitrates, sulfates, etc., as long as it is soluble in water and releases metal ions in the aqueous solution. The concentration of the precursor solution containing metal cations depends on the metal loading, and the present invention does not impose specific limitations. Those skilled in the art can select and adjust it according to the actual situation.
[0015] In the preparation method of the sodium-resistant selective molecular sieve of the present invention, the metal is calculated as oxide, and the metal loading is 0.1-5 wt% of the molecular sieve mass.
[0016] The preparation method of the sodium-resistant type-selective molecular sieve described in this invention does not specifically limit the impregnation method; conventional impregnation methods in the art can be used. Preferably, when impregnating the molecular sieve with a precursor solution containing phosphorus anions, equal-volume impregnation is performed at room temperature. When impregnating with a precursor solution containing metal cations and an alkaline organic ammonium salt solution, impregnation is performed at high temperature. Preferably, the impregnation temperature is 80-200℃. Impregnation within this temperature range can promote metal dispersion and the removal of a small amount of Si from the molecular sieve. Simultaneously, the organic ammonium cations, because they cannot enter the molecular sieve pores, act as a protective agent to protect the molecular sieve surface, allowing more metal to disperse within the pores and ensuring the anti-fouling performance of the active centers inside the molecular sieve. After impregnation, drying and calcination are performed. Drying and calcination are conventional technical operations in the art. Those skilled in the art can select and adjust the drying and calcination temperatures and times according to actual conditions and conventional technical knowledge in the art; these are not specifically limited in this invention.
[0017] The method for preparing sodium-resistant selective molecular sieves according to the present invention uses rotary evaporation impregnation or rotary crystallization when impregnating with a precursor solution containing metal cations and an alkaline organic ammonium salt solution.
[0018] The beneficial effects of this invention are:
[0019] The method described in this invention introduces metal cations into the molecular sieve to interact with the acidic centers on the sieve surface, thereby stabilizing the acidic centers. Simultaneously, the metal cations themselves act as a sacrificial agent, undergoing slight loss under high-severity exchange conditions (a reduction of 0.1-0.2 wt% in loading before and after contamination), protecting the acidic centers on the molecular sieve surface from Na contamination. This method also introduces a small amount of template agent while dispersing the metal, hindering surface loading and maximizing metal dispersion within the pores. Combined with phosphorus (P), this maximizes the anti-contamination capability of the acidic centers within the pores. Furthermore, the metal cations introduced into this Na-resistant molecular sieve, while interacting with the acidic centers formed on the sieve surface, more readily combine with Na ions, attracting more Na ions to non-acidic centers and avoiding the poisoning effect of acidic centers during experiments. Therefore, the prepared catalytic cracking catalyst can effectively avoid a significant decrease in catalyst activity caused by Na contamination in industrial applications. Detailed Implementation
[0020] The present invention will now be described in detail through embodiments. It should be noted that the following embodiments are only for further illustration of the present invention and should not be construed as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above description.
[0021] (I) Source of raw materials or equipment: Industrial ZSM-5 molecular sieve (low-silica ZSM-5 molecular sieve, high-silica ZSM-5 molecular sieve, nano ZSM-5 molecular sieve, industrial grade molecular sieve, all provided by Lanzhou Petrochemical Catalyst Plant), NaCl (Sinopharm), diammonium hydrogen phosphate (Sinopharm), boehmite (industrial grade, Lanzhou Petrochemical Catalyst Plant), cobalt nitrate hexahydrate (Sinopharm), magnesium chloride, hexahydrate (Sinopharm), zinc chloride (Sinopharm), tetrapropylammonium hydroxide (Sinopharm).
[0022] (II) Analysis and Evaluation Methods:
[0023] 1. Main Analytical Methods
[0024] The changes in Na2O, P2O5, and metal oxide content in different molecular sieves before and after high-criticality exchange were investigated using X-ray fluorescence (XRF) testing. The Na2O content in the catalyst was characterized by the determination of sodium oxide, rare earth oxide, and aluminum oxide content in catalytic cracking catalysts (standard code: Q / SY LS1050).
[0025] 2. Sodium ion contamination test of molecular sieves
[0026] To simulate the effect of Na-containing catalyst slurry on molecular sieves during the synthesis process within the 30-80℃ range, a sodium ion contamination test was conducted. The steps were as follows: A 1wt% NaCl aqueous solution was prepared, and the molecular sieve to be tested was mixed with the prepared NaCl aqueous solution at a ratio of 1:10. After the molecular sieve was evenly dispersed, the mixture was continuously stirred in a water bath at 85℃ for 2 hours. The mixture was then filtered, dried, and calcined to obtain the sodium ion contaminated molecular sieve.
[0027] 3. Sodium ion contamination test of catalyst
[0028] To simulate the effect of Na-containing feedstock on catalyst reactivity during industrial applications, a sodium ion loading test was conducted on the catalyst. The steps were as follows: A NaCl aqueous solution with a loading of 0.7 wt% Na₂O (approximately 7000 ppm industrially) was prepared according to the catalyst's water absorption capacity. An equal volume of this solution was then impregnated onto the catalyst after calcination at 600°C for 2 hours. The catalyst was then dried and calcined again at 600°C for 2 hours. Uncontaminated catalysts were calcined at 600°C for 4 hours. Catalysts before and after sodium ion contamination were obtained.
[0029] 4. Catalyst evaluation test
[0030] The reaction performance was evaluated using an ACE apparatus. Before evaluation, the catalyst was aged at 800℃ for 17 hours. The feedstock oil used was ACE standard oil, the reaction temperature was 530℃, and the catalyst-to-oil ratio was 6.
[0031] Conversion rate (wt%) = 100 (wt%) - Heavy oil yield (wt%) - Diesel yield (wt%);
[0032] C2-C4 olefin yield (wt%) = ethylene yield (wt%) + propylene yield (wt%) + butene yield (wt%);
[0033] Example 1
[0034] Take 80g of low-silica ZSM-5 molecular sieve (LS-ZSM-5) and prepare 50g of ammonium dihydrogen phosphate aqueous solution (47.9g water and 2.1g ammonium dihydrogen phosphate). Impregnate the LS-ZSM-5 molecular sieve with an equal volume of solution. After impregnation, dry (90℃) to obtain P / LS-ZSM-5 molecular sieve. Take 40g of P / LS-ZSM-5 molecular sieve and add 100g of 5wt% tetrapropylammonium hydroxide (TPAOH) aqueous solution and 25g of zinc chloride aqueous solution (24.4g water and 0.6g zinc chloride). Stir and impregnate the P / LS-ZSM-5 molecular sieve with rotary evaporation in an oil bath at 90℃. After impregnation, dry (90℃) and calcine (500℃, 1h) to obtain P-Zn / LS-ZSM-5 molecular sieve.
[0035] Example 2
[0036] Take 80g of low-silica ZSM-5 molecular sieve (LS-ZSM-5) and prepare 50g of ammonium dihydrogen phosphate aqueous solution (48.7g water and 1.3g ammonium dihydrogen phosphate). Impregnate the LS-ZSM-5 molecular sieve with an equal volume of solution. After impregnation, dry (90℃) to obtain P / LS-ZSM-5 molecular sieve. Take 40g of P / LS-ZSM-5 molecular sieve and add 80g of 5wt% TPAOH aqueous solution and 25g of magnesium chloride aqueous solution (23.4g water and 1.6g magnesium chloride, hexahydrate). Stir and impregnate the P / LS-ZSM-5 molecular sieve with rotary evaporation in an oil bath at 90℃. After impregnation, dry (90℃) and calcine (500℃, 1h) to obtain P-Mg / LS-ZSM-5 molecular sieve.
[0037] Example 3
[0038] Take 80g of low-silica ZSM-5 molecular sieve (LS-ZSM-5) and prepare 50g of ammonium dihydrogen phosphate aqueous solution (47.0g water and 3.0g ammonium dihydrogen phosphate). Impregnate the LS-ZSM-5 molecular sieve with an equal volume of solution. After impregnation, dry (90℃) to obtain P / LS-ZSM-5 molecular sieve. Take 40g of P / LS-ZSM-5 molecular sieve and add 150g of 5wt% TPAOH aqueous solution and 26g of cobalt nitrate aqueous solution (24.5g water and 1.5g cobalt nitrate hexahydrate). Stir and impregnate the P / LS-ZSM-5 molecular sieve with rotary evaporation in an oil bath at 90℃. After impregnation, dry (90℃) and calcine (500℃, 1h) to obtain P-Co / LS-ZSM-5 molecular sieve.
[0039] Example 4
[0040] Take 80g of high-silica ZSM-5 molecular sieve (HS-ZSM-5) and prepare 60g of ammonium dihydrogen phosphate aqueous solution (59.3g water and 0.7g ammonium dihydrogen phosphate). Impregnate the HS-ZSM-5 molecular sieve with an equal volume of solution. After impregnation, dry (90℃) to obtain P / HS-ZSM-5 molecular sieve. Take 40g of P / HS-ZSM-5 molecular sieve and add 100g of 5wt% TPAOH aqueous solution and 30g of zinc chloride aqueous solution (29.7g water and 0.3g zinc chloride). Stir and impregnate the P / HS-ZSM-5 molecular sieve with rotary evaporation in an oil bath at 90℃. After impregnation, dry (90℃) and calcine (500℃, 1h) to obtain P-Zn / HS-ZSM-5 molecular sieve.
[0041] Example 5
[0042] Take 80g of nano ZSM-5 molecular sieve (N-ZSM-5) and prepare 68g of ammonium dihydrogen phosphate aqueous solution (64.6g water and 3.4g ammonium dihydrogen phosphate). Impregnate the N-ZSM-5 molecular sieve with an equal volume of solution. After impregnation, dry (90℃) to obtain P / N-ZSM-5 molecular sieve. Take 40g of P / N-ZSM-5 molecular sieve and add 100g of 20wt% benzyltrimethylammonium hydroxide aqueous solution and 30g of zinc chloride aqueous solution (28.8g water and 1.2g zinc chloride). Stir and place the mixed solution in a 250mL crystallization vessel. Perform rotary crystallization at 170℃ for 24h. After crystallization, separate, dry (90℃), and calcine (500℃, 1h) to obtain P-Zn / N-ZSM-5 molecular sieve.
[0043] Example 6
[0044] Consistent with Example 1, except that 50g of ammonium phosphate aqueous solution (46.3g of water and 3.7g of triammonium phosphate, trihydrate) was used in the phosphorus loading stage to finally obtain P-Zn / LS-ZSM-5 molecular sieve (2).
[0045] Example 7
[0046] Consistent with Example 1, except that 50g of phosphoric acid aqueous solution (47.6g of water and 2.4g of 75% phosphoric acid) was used in the phosphorus loading stage to finally obtain P-Zn / LS-ZSM-5 molecular sieve (3).
[0047] Example 8
[0048] Consistent with Example 1, except that 50g of diammonium hydrogen phosphate aqueous solution (47.6g water and 2.4g diammonium hydrogen phosphate) was used in the phosphorus loading stage to finally obtain P-Zn / LS-ZSM-5 molecular sieve (4).
[0049] Example 9
[0050] Consistent with Example 1, except that the mixed solution used in the metal loading stage was 100g of 5wt% tetrapropylammonium hydroxide (TPAOH) aqueous solution and 25g of ferric chloride aqueous solution (21.5g of water and 3.5g of ferric chloride hexahydrate), which was stirred to finally obtain P-Fe / LS-ZSM-5 molecular sieve.
[0051] Example 10
[0052] Consistent with Example 1, except that the mixed solution used in the metal loading stage was 100g of 5wt% tetrapropylammonium hydroxide (TPAOH) aqueous solution and 25g of nickel chloride aqueous solution (23.5g of water and 1.5g of nickel chloride, hexahydrate), which was stirred to finally obtain P-Ni / LS-ZSM-5 molecular sieve.
[0053] Example 11
[0054] Consistent with Example 1, except that the mixed solution used in the metal loading stage was 100g of 5wt% tetrapropylammonium hydroxide (TPAOH) aqueous solution and 25g of copper nitrate aqueous solution (23.0g water and 2.0g copper nitrate, trihydrate), which was stirred to finally obtain P-Cu / LS-ZSM-5 molecular sieve.
[0055] Comparative Example 1
[0056] Similar to Example 1, except that during the metal loading stage, 125g of zinc chloride aqueous solution (124.4g of water and 0.6g of zinc chloride) was added to the P / LS-ZSM-5 molecular sieve and stirred. The P / LS-ZSM-5 molecular sieve was then subjected to rotary evaporation impregnation in an oil bath at 90°C. After impregnation, the sieve was dried (90°C) and calcined (500°C, 1h) to obtain P-Zn / LS-ZSM-5 molecular sieve (5).
[0057] Comparative Example 2
[0058] Similar to Example 1, except that in the metal loading stage, another 40g of the corresponding impregnated P low silica ZSM-5 molecular sieve (LS-ZSM-5) was taken, and 34g of zinc chloride aqueous solution (33.4g water and 0.6g zinc chloride) was prepared. The P / LS-ZSM-5 molecular sieve was impregnated at room temperature, dried (90°C), and calcined (500°C, 1h) to obtain P-Zn / LS-ZSM-5 molecular sieve (6).
[0059] Comparative Example 3
[0060] Similar to Example 1, except that the molecular sieve is not loaded with metal, 40g of the corresponding low-silica ZSM-5 molecular sieve impregnated with P is directly taken, impregnated with 34g of deionized water, dried (90°C), and calcined (500°C, 1h) to obtain P / LS-ZSM-5 molecular sieve.
[0061] Comparative Example 4
[0062] Similar to Comparative Example 1, except that the molecular sieve is not loaded with phosphorus, 40g of LS-ZSM-5 molecular sieve was directly taken, and 25g of zinc chloride aqueous solution (24.4g water and 0.6g zinc chloride) was prepared. The LS-ZSM-5 molecular sieve was impregnated by rotary evaporation in an oil bath at 90℃, and then dried (90℃) and calcined (500℃, 1h) to obtain Zn / LS-ZSM-5 molecular sieve.
[0063] Comparative Example 5
[0064] Similar to Example 1, except that 40g of P / LS-ZSM-5 molecular sieve was taken and 100g of 25wt% tetrapropylammonium hydroxide (TPAOH) aqueous solution and 25g of zinc chloride aqueous solution (24.4g water and 0.6g zinc chloride) were added and stirred. The P / LS-ZSM-5 molecular sieve was impregnated by rotary evaporation in an oil bath at 90°C. After impregnation, it was dried (90°C) and calcined (500°C, 1h) to obtain P-Zn / LS-ZSM-5 molecular sieve (7).
[0065] Table 1. Sodium oxide content of different molecular sieves after sodium contamination.
[0066]
[0067] As shown in Table 1, the molecular sieves prepared in Examples 1-8 all exhibited relatively excellent resistance to Na contamination. The molecular sieves prepared in Examples 9-11 showed some resistance to Na contamination, but there was a certain gap compared to Examples 1-9. Compared to Example 1, the resistance to Na contamination in Comparative Example 1 decreased to some extent, indicating that the addition of a certain amount of template agent protected the stability of the anti-sodium element on the surface of the molecular sieve under high-temperature treatment. Compared to Comparative Example 1, the resistance to Na contamination in Comparative Example 2 further decreased, indicating that the better dispersion of metals in Examples 1 and Comparative Example 1 helped the molecular sieve resist sodium. Comparative Example 3 showed that the second metal had a significant impact on the Na resistance of the molecular sieve. Comparative Example 4 showed that a single metal load did not have excellent anti-sodium performance. In Comparative Example 5, when the amount of template agent added was too large, it led to a decrease in the Zn loading (the actual measured ZnO content was 50% lower than that in Example 1), and the high concentration of alkaline template agent during high-temperature treatment would affect the stability of the molecular sieve's own framework.
[0068] To further demonstrate the anti-Na contamination ability of catalysts prepared from different molecular sieves in practical industrial applications, ZSM-5 molecular sieves prepared in Example 1, Comparative Example 1, and Comparative Example 2 were selected as key materials to prepare three catalytic cracking catalysts to verify their anti-contamination ability. Specific preparation schemes are detailed in Example 12, Comparative Example 6, and Comparative Example 7. Na contamination tests were conducted on the three catalysts, and the ACE (acetylene ionization) of the six catalysts before and after contamination was evaluated. The specific implementation and evaluation results are as follows:
[0069] Example 12
[0070] The catalytic cracking catalyst was prepared using the molecular sieves described in Example 1. The process included mixing and slurrying 85g of Y molecular sieve (commercial brand ReUSY, Lanzhou Petrochemical Catalyst Plant); 71g of ZSM-5 molecular sieve (Example 1 P-Zn / LS-ZSM-5 molecular sieve); 125g of alumina sol (Lanzhou Petrochemical Catalyst Plant); 142.8g of kaolin (Lanzhou Petrochemical Catalyst Plant); and 436.9g of chemically treated water to obtain a molecular sieve slurry. Then, 71.2g of boehmite (Lanzhou Petrochemical Catalyst Plant) and 55g of hydrochloric acid (36% concentration) were added, and the mixture was aged at 50℃ for 1 hour to obtain a matrix slurry. The molecular sieve slurry and the matrix slurry were mixed, slurryed for 10 minutes, homogenized, spray-dried, calcined, washed, and dried to obtain the catalytic cracking catalyst. The catalyst was then directly calcined at 600℃ for 4 hours.
[0071] Comparative Example 6
[0072] The specific preparation scheme of the catalyst is the same as that in Example 12, except that the ZSM-5 molecular sieve used is the P-Zn / LS-ZSM-5(5) molecular sieve of Comparative Example 1.
[0073] Comparative Example 7
[0074] The specific preparation scheme of the catalyst is the same as that in Example 12, except that the ZSM-5 molecular sieve used is the P-Zn / LS-ZSM-5(6) molecular sieve of Comparative Example 2.
[0075] Table 2. Na content analysis results of catalysts in Example 12 and Comparative Examples 6-7
[0076]
[0077] Table 3. ACE evaluation results of catalysts in Example 12 and Comparative Examples 6-7
[0078]
[0079] Table 2 shows the Na content analysis results of the catalysts in Example 12 and Comparative Examples 6-7. As can be seen from Table 2, after Na contamination loading, the sodium oxide content of the catalysts does not differ much, ranging from 0.82 to 0.83 wt%, to simulate Na contamination during the industrial application of the catalysts.
[0080] Table 3 shows the ACE evaluation results of the catalysts in Example 12 and Comparative Examples 6-7. As can be seen from Table 3, the data for the catalyst prepared in Example 12 before and after Na contamination showed little deviation, indicating that the catalyst has excellent sodium resistance. Furthermore, the catalyst in Example 12, due to the action of the alkaline template agent, promoted the diffusion of reaction products within the molecular sieve, thus contributing to diesel and gasoline conversion. Comparing the evaluation results of the catalysts after Na contamination, the propylene yield of Comparative Example 6 was 1.36 units lower than that of Example 12, indicating that, with similar sodium resistance, the acidic centers within the molecular sieve pores were better protected. In addition, the evaluation results of the catalysts in Comparative Examples 6 and 7 before and after Na contamination showed significant fluctuations in propylene and gasoline yields. In particular, the gasoline yield of Comparative Example 7 increased by 0.9 units while the propylene yield decreased by 1.47 units, indicating that Na contamination reduced the catalyst's gasoline conversion capacity and also reduced the shape selectivity of key materials in the catalyst, thus leading to a decrease in propylene yield.
[0081] Of course, the present invention may have other various embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications according to the present invention, but these corresponding changes and modifications should all fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a sodium-resistant molecular sieve, characterized in that, Molecular sieves are impregnated with a precursor solution containing phosphorus anions and dried to obtain phosphorus-modified molecular sieves. The phosphorus-modified molecular sieves are then impregnated with a precursor solution containing metal cations and an alkaline organic ammonium salt solution, and then dried and calcined to obtain sodium-resistant molecular sieves. The alkaline organic ammonium salt is one or more selected from tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, benzyltrimethylammonium hydroxide, tetraethylammonium hydroxide, and tetramethylammonium hydroxide; The mass ratio of the alkaline organic ammonium salt to the phosphorus-modified molecular sieve is 0.01-0.5; The metal in the precursor containing metal cations is one or more of Fe, Co, Ni, Zn, Mg, and Cu.
2. The method for preparing the sodium-resistant molecular sieve according to claim 1, characterized in that, The molecular sieve is one or more of ZSM-5 molecular sieve, Y molecular sieve, and β molecular sieve.
3. The method for preparing the sodium-resistant molecular sieve according to claim 1, characterized in that, The phosphorus-containing anion precursor is one or more of ammonium phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, phosphoric acid, and ammonium trihydrogen phosphate.
4. The method for preparing the sodium-resistant molecular sieve according to claim 1, characterized in that, Phosphorus, expressed as oxides, is loaded at a rate of 1-5 wt% of the molecular sieve mass.
5. The method for preparing the sodium-resistant molecular sieve according to claim 1, characterized in that, The metal in the precursor containing the metal cation is one or more of Co, Zn, and Mg.
6. The method for preparing the sodium-resistant molecular sieve according to claim 1, characterized in that, The metal is expressed as an oxide, and the metal loading is 0.1-5 wt% of the molecular sieve mass.
7. The method for preparing the sodium-resistant molecular sieve according to claim 1, characterized in that, The impregnation temperature for impregnation with precursor solutions containing metal cations and alkaline organic ammonium salt solutions is 80-200℃.
8. The method for preparing the sodium-resistant molecular sieve according to claim 1, characterized in that, When impregnating with a precursor solution containing metal cations and an alkaline organic ammonium salt solution, the impregnation method is rotary evaporation impregnation or rotary crystallization.
Citation Information
Patent Citations
Modified molecular sieve capable of improving sodium pollution resisting capability and preparation method of modified molecular sieve
CN102050458A
Super stable y-type molecular sieve cracking catalyst containing rare earths oxidate
CN86107598A
Method for preparing self-supporting metal-modified ZSM-5 molecular sieve and application of self-supporting metal-modified ZSM-5 molecular sieve to synthesis of isoprene
CN107961812A
Double-component modification method of molecular sieve in FCC catalyst and molecular sieve modified through method
CN110116021A